Lecture assessment system(report module) - Selamat, Norhanim (2003)
Nowadays, basically software development for web-based assessment system is based on user requirements in a university or institution. Mostly, the existing system provided for test evaluation for a programming language or on-line assessment. But, to find a web-based system that fulfill the requirements such as able to assist the lecturers input assessment mark, to manipulate calculation automatically, to provide a list of attendance student, to produce a warning letter for an absence student and to monitor the teaching and learning progress in a university is difficult. Therefore, Lecture Assessment System (LAS) were developed to fulfill the requirements for the users in Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO) that are administration and lecturers.